"Laser Sintering of Unimodal Distributed Glass Powders of Different Size". (2015) - Sofia, Daniele; Granese, Mirko; Barletta, Diego; Poletto, Massimo
Abstract: In the present paper heat exchange rates for selective laser melting/sintering (SLM/SLS) of glass beads were evaluated. Experiments were carried out with a nominal 40W CO2 laser, on samples characterized by different particle size distributions within16 and184 μm, and different laser scan speeds (1-30 mm s -1 ). The energy required for the sintering process depends on the particle size. In particular, part of the energy supplied by the laser beam is dispersed by different mechanisms of energy transfer. These quantities were estimated to evaluate the process effectiveness in particle melting or sintering. On this purpose the energy balance was solved by combining experimental data and exchange coefficients calculated from known empirical correlations. The amount of the molten mass changes with particle size and maximum is observed for the sample with average particle size of 48 μm. The increase of the molten mass between 16 μm and 48 μm is 24% at a scan speed of 1 mm s -1 and it is 47% at a scan speed of 5 mm s -1 .